Hague Yearbook of International Law - Vidmar, Jure (Hague Yearbook of International Law / Annuaire de La Haye de Droit International, 2019)
The aim of the Hague Yearbook of International Law is to offer a platform for review of new developments in the field of international law. In addition, it devotes attention to developments in the international law institutions based in the international City of Peace and Justice, The Hague. As of the 2010 Volume, the Yearbook has been compiled by a new and expanded Editorial Board, offering fresh ideas and a new approach. A newly established Advisory Board has also been added, including leading judges, practitioners and scholars. Sections have been created on public international law, private international law, international investment law and international criminal law, containing in-depth articles on current issues. The breadth of the Yearbook's content thus offers an interesting and valuable illustration of the dynamic developments in the various sub-areas of international law.